2002
DOI: 10.1002/cncr.10437
|View full text |Cite
|
Sign up to set email alerts
|

A multiinstitutional, concurrent chemoradiation trial of strontium‐89, estramustine, and vinblastine for hormone refractory prostate carcinoma involving bone

Abstract: A novel process for hydrogen generation from water at high conversion is presented that is based on zinc hydrolysis as part of the two‐step water‐splitting thermochemical cycle of Zn/ZnO redox reactions. It encompasses formation of Zn nanoparticles by steam‐quenching a Zn(g) flow followed by in situ hydrolysis. The process is experimentally demonstrated at the laboratory scale using a tubular aerosol flow reactor featuring a Zn‐evaporation, a mixing and a reaction zone. In the reaction zone, operated at and ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 38 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…Most studies regarding Sr-89 involved patients who had received chemotherapy before Sr-89 administration, presenting it as a background factor. Akerley et al (13), Tu et al (14) and Sciuto et al (15) reported simultaneous combination therapy with Sr-89 and chemotherapeutic agents in patients with prostate cancer and observed tolerance. Furthermore, Tu et al (16) and Porfini et al (17) investigated whether or not chemotherapy can be performed after Sr-89 administration in prostate cancer patients, and concluded that chemotherapy was possible.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies regarding Sr-89 involved patients who had received chemotherapy before Sr-89 administration, presenting it as a background factor. Akerley et al (13), Tu et al (14) and Sciuto et al (15) reported simultaneous combination therapy with Sr-89 and chemotherapeutic agents in patients with prostate cancer and observed tolerance. Furthermore, Tu et al (16) and Porfini et al (17) investigated whether or not chemotherapy can be performed after Sr-89 administration in prostate cancer patients, and concluded that chemotherapy was possible.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 NCI-3410 is a Phase III trial to compare the effectiveness of chemotherapy with or without strontium-89 in treating patients who have prostate cancer that has spread to the bone. 54 Patients receive one of two chemotherapy regimens for 6 weeks.…”
Section: Local and Systemic Radiation For Palliationmentioning
confidence: 99%
“…These radionuclides are betaemitting radioisotopes that differ primarily in their radioactive half-lives and the tissue penetrance of their beta particles. Adding systemic radioisotopes to chemotherapy regimens for patients with advanced prostate cancer appears to increase response rates and survival [Tu et al, 2001;Akerley et al, 2002]. Further exploration of how this could be applied to the human disease setting is being investigated in preclinical and clinical settings.…”
Section: Targeting the Stromal Cellsmentioning
confidence: 99%